2015
DOI: 10.1016/j.jalz.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin‐releasing factor receptor‐1 antagonism mitigates beta amyloid pathology and cognitive and synaptic deficits in a mouse model of Alzheimer's disease

Abstract: INTRODUCTION Stress and corticotropin-releasing factor (CRF) have been implicated as mechanistically involved in Alzheimer’s disease (AD), but agents that impact CRF signaling have not been carefully tested for therapeutic efficacy or long term safety in animal models. METHODS To test whether antagonism of the type-1 CRF receptor (CRFR1) could be used as a disease-modifying treatment for AD, we used a preclinical prevention paradigm and treated 30-day-old AD transgenic (AD) mice with the small molecule, CRFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 52 publications
0
35
0
Order By: Relevance
“…It is well established that the specific transgenic mouse model used in this study (PSAPP) develops A β deposits by 2–3 months of age with reliable onset of A β neuritic plaques at 6 months of age (Jankowsky et al, 2004; Zhang et al, 2016). Using Thioflavin S–stained coronal sections and densitometry, we confirmed that vehicle-treated female PSAPP mice at 9 months of age demonstrated significant accumulation of A β plaques (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that the specific transgenic mouse model used in this study (PSAPP) develops A β deposits by 2–3 months of age with reliable onset of A β neuritic plaques at 6 months of age (Jankowsky et al, 2004; Zhang et al, 2016). Using Thioflavin S–stained coronal sections and densitometry, we confirmed that vehicle-treated female PSAPP mice at 9 months of age demonstrated significant accumulation of A β plaques (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the etomidate-caused inhibition of 11-β-hydroxylase increases substrate availability for synthesis of GABAergic neuroactive steroids, which by enhancing GABA A R-mediated depolarization/stimulation in the hypothalamus of neonatal rats may further increase production of corticotropin-releasing hormone (CRH) (Kaminski and Rogawski MA, 2001). An increase in CRH production is not only a crucial initial step in the activation of the LHPA axis by stress, but may also contribute to a number of neurodevelopmental abnormalities by acting outside of the LHPA axis (Toth et al , 2014; Flandreau et al , 2015; Zhang et al , 2016). …”
Section: Introductionmentioning
confidence: 99%
“…; Zhang et al . ). Such data has led to studies examining the repurposing of agents that block corticotropin releasing factor (CRF) signaling as well as strategies supporting direct targeting of CRF (Park et al .…”
Section: Obstacle 8: Little Insight Into the Biological Underpinningsmentioning
confidence: 97%
“…Indeed, future preclinical and translational human studies of how factors like infection, psychological stress, head trauma, and diet may provide important clues that could be harnessed into a novel intervention that may or may not be pharmacologic in nature. One interesting example of how relatively challenging epidemiologic data relating stress to risk of AD has gained a foothold in the AD research landscape are studies showing that stress promotes both Ab and tau pathology in mice and does so through a corticotropin-releasing factor based mechanism (Kang et al 2007;Carroll et al 2011;Dong et al 2012;Greenberg et al 2014;Park et al 2015;Zhang et al 2015). Such data has led to studies examining the repurposing of agents that block corticotropin releasing factor (CRF) signaling as well as strategies supporting direct targeting of CRF (Park et al 2015;Zhang et al 2015).…”
Section: Obstacle 8: Little Insight Into the Biological Underpinningsmentioning
confidence: 99%